FORMULATION AND EVALUATION OF IMPLANTABLE DRUG DELIVERY SYSTEM OF TEMOZOLOMIDE BY USING HYDROPHILIC POLYMER - V, Sindhu; S, Bhavya; P, Suresh Kumar; M, Jeyabaskaran; T, Praveenkumar; Sulthana, Sd. Yasmin (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: The present research study was carried out to formulate and evaluate the implants of temozolomide using hydrophilic polymer. Methods: Temozolomide implants were formulated using extrusion method with different grades of carbopol. The powdered blend was evaluated for micromeritic properties such as angle of repose, bulk density, tapped density, Carr's index, and Hausner's ratio. The formulated implants were analyzed for drug content uniformity, thickness, weight variation, and short-term stability study. In vitro release study of implants was performed using 0.1N hydrochloric acid, and it is maintained at 37Â°CÂ±0.5Â°C. Results: In vitro release study demonstrated that the release rate of temozolomide from the implant matrix was a function of concentration of the polymer. As the concentration of polymer was increased, drug release from the matrix was extended. The release of drug from all implant formulations was found to be uniform and was extended over a period of 12 hrs. The implant formulations were found sterile, uniform in weight and size. The drug content was found to be in the range of 97.2-101.33%. Conclusion: Drug interaction studies revealed that there were no chemical interactions between temozolomide and polymers used in the study. Short-term stability studies of implants revealed that implants were stable, and there were no significant changes in the physical appearance and drug content of the implant formulations. The results of the study demonstrated that implantable drug delivery system of temozolomide can be formulated using hydrophilic polymer.